Targeted HIV seroprevalence among Vietnamese in southern California. Issue 4 (August 1994) - Gellert, G A; Moore, D F; Maxwell, R M; Mai, K K; Higgins, K V
Abstract : OBJECTIVE--The prevalence of HIV among southern California Vietnamese is unknown. We collected seroprevalence data on targeted Vietnamese in Orange County, California who may be at risk for HIV infection. METHODS--The assumption of elevated risk was based on rates of infection reported among other U.S. groups. Vietnamese (N = 874) from six county sites were tested during 1992: (1) attendees at county HIV/STD clinics and (2) IDU program; (3) male inmates of the county jail and (4) of a juvenile detention centre; (5) males in a driving under the influence of alcohol (DUI) remedial program; and (6) patients for nonpregnancy-related syphilis screening. RESULTS--The number of cases detected and risk factors were: (1) county HIV/STD clinics--5/223 (2.3%), all men who had sex with men; (2) men's jail--1/122 (0.8%), risk factors unknown; (3) juvenile hall--1/145 (0.7%), risk factors unknown; (4) IDU program--0/33; (5) syphilis screening--0/284; and (6) DUI program--0/67. CONCLUSIONS--HIV infection exists among southern California Vietnamese, and men who have sex with men appear to be at a risk for HIV infection similar to others practicing high risk behaviors in the U.S. population. Preventive education needs to be targeted explicitly at these individuals.